A human tRNA methyltransferase 9‐like protein prevents tumour growth by regulating LIN9 and HIF1‐α. Issue 3 (4th February 2013) - Begley, Ulrike; Sosa, Maria Soledad; Avivar‐Valderas, Alvaro; Patil, Ashish; Endres, Lauren; Estrada, Yeriel; Chan, Clement T.Y.; Su, Dan; Dedon, Peter C.; Aguirre‐Ghiso, Julio A.; Begley, Thomas
Abstract Emerging evidence points to aberrant regulation of translation as a driver of cell transformation in cancer. Given the direct control of translation by tRNA modifications, tRNA modifying enzymes may function as regulators of cancer progression. Here, we show that a tRNA methyltransferase 9‐like (hTRM9L/KIAA1456) mRNA is down‐regulated in breast, bladder, colorectal, cervix and testicular carcinomas. In the aggressive SW620 and HCT116 colon carcinoma cell lines, hTRM9L is silenced and its re‐expression and methyltransferase activity dramatically suppressed tumour growth in vivo. This growth inhibition was linked to decreased proliferation, senescence‐like G0/G1‐arrest and up‐regulation of the RB interacting protein LIN9. Additionally, SW620 cells re‐expressing hTRM9L did not respond to hypoxia via HIF1‐α‐dependent induction of GLUT1. Importantly, hTRM9L‐negative tumours were highly sensitive to aminoglycoside antibiotics and this was associated with altered tRNA modification levels compared to antibiotic resistant hTRM9L‐expressing SW620 cells. Our study links hTRM9L and tRNA modifications to inhibition of tumour growth via LIN9 and HIF1‐α‐dependent mechanisms. It also suggests that aminoglycoside antibiotics may be useful to treat hTRM9L‐deficient tumours.